PENGARUH KEPUTUSAN INVESTASI, LIKUIDITAS, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Jannah, Isnawati Miftahul; Febyansyah, Andar (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study is to identify the factors that influence firm value. This study examines the effect of investment decisions, liquidity, firm size and capital structure on firm value in property and real estate subsector service companies listed on the Indonesia Stock Exchange for the 2020-2022 period. With the purposive sampling method, there were 159 data samples that met the population criteria in this study. Descriptive statistical analysis and multiple linear regression analysis were carried out in this study using the SPSS Statistic 29 data processing application. The results showed that investment decision and liquidity variables had an effect on firm value, while firm size and capital structure had no effect on firm value.